Pengaruh Pendidikan Literasi Keuangan Terhadap Perencanaan Keuangan Siswa Sekolah Muslim Santitham, Thailand Selatan. - Sofiyani, Putri; Saraswati, Henny; Hillalliyati, Najmi; Shumalee, Shakirin (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2024)
This research aimed to examine the influence of financial literacy and behavior on students' financial planning at the Muslim Santitham Foundation School. Adopting a quantitative method, questionnaires were used as the primary data collection instrument. A total of 100 students from Matthayom levels 4 to 6 were purposively selected as the respondents. The results showed that financial literacy had a positive and significant impact on students' financial planning skills. In contrast, financial behavior, while showing a positive effect, did not significantly influence their planning. Despite financial literacy not being explicitly integrated into the school curriculum, the students demonstrated a satisfactory understanding of the basic principles of personal financial management. This research addressed a critical gap by exploring how financial literacy contributed to shaping planning among students, particularly within a cultural context where discussing financial matters was relatively new.